Exploring the Role of WhatsApp in Shaping Ethical Communication Practices within Higher Education Institutions - Primardiana Hermilia Wijayati; Dewi Kartika Ardiyani; Reza Safitri; Zanakulov Zayniddin (Nexus Publishing, 2026)
Social media has become one of the most dominant communication tools, especially among academics. WhatsApp, as one of the most widely used instant messaging platforms, has become an essential means for lecturers and students to interact academically. This paper presents the results of a study aimed at exploring the attitudes and behaviors of students and lecturers in communicating through WhatsApp groups. This study employed a quantitative descriptive method, with a questionnaire instrument distributed online to lecturers and students of the German Literature Department. There were 199 respondents who were willing to fill out the questionnaire. Findings reveal that the types of messages frequently shared in the group are questions about course materials and assignments. A majority of students demonstrate openness and honesty in admitting mistakes, maintain impartiality during non-conducive communication situations, and exhibit high vigilance toward prize offer messages from unknown sources by blocking or rejecting them. However, only a small proportion of users consistently respond to messages sent by other group members in academic WhatsApp groups. There is a notable tendency to avoid direct confrontation to preserve social harmony, which presents an ethical dilemma between openness and maintaining interpersonal relationships.